1999
DOI: 10.1002/ls.3010110202
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical modification of zinc carboxylate‐containing lubricants by molecular structure changes

Abstract: Twenty‐two samples of zinc carboxylates were prepared from saturated, non‐cyclic carboxylic acids with systematically altered hydrocarbon chain structures under well‐defined conditions. Essential temperature‐ and solvent‐induced changes concerning the coordination of the carboxylate group are shown using selected prepared samples, and general rules for systems containing zinc carboxylates in nonpolar media are presented. It is shown that there are three possible structural forms for zinc carboxylates: polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The migrating Sn species during reaction are hypothesized to be volatile tin carboxylates formed via the reaction between SnO x species and heptanoic acid. 35 These tin species may decompose on Pd sites located on and within nearby silica particles or simply be deposited on the silica support. 35 The and Van Krevelen mechanism (Scheme 1D).…”
Section: Activity Of Pdsn Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The migrating Sn species during reaction are hypothesized to be volatile tin carboxylates formed via the reaction between SnO x species and heptanoic acid. 35 These tin species may decompose on Pd sites located on and within nearby silica particles or simply be deposited on the silica support. 35 The and Van Krevelen mechanism (Scheme 1D).…”
Section: Activity Of Pdsn Catalystsmentioning
confidence: 99%
“…35 These tin species may decompose on Pd sites located on and within nearby silica particles or simply be deposited on the silica support. 35 The and Van Krevelen mechanism (Scheme 1D). [36][37][38] Addition of a metal capable of hydrogen spillover, such as Pt, facilitates reduction of the metal oxide, thus promoting aldehyde formation.…”
Section: Activity Of Pdsn Catalystsmentioning
confidence: 99%
“…However, under water-free conditions, these zinc salts exist in a linear coordination polymer structure (referred to as “chain complex,” shown in Fig. 1F) ( 23 ). We were able to reproduce the spectral features of the chain and oxo complex in liquid zinc palmitate (ZnPa; zinc hexadecanoate).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, ν as (COO − ) (1531 cm −1 ) and ν s (COO − ) (1403 cm −1 ) of the syn‐syn bridged carboxylate groups become very weak. Some reports have shown that zinc oxocarboxylates (Zn 4 O(OOCR) 6 , R = alkyl or aryl) can be formed when zinc carboxylates were treated in a hot ketone solution 36, 40. The Zn 4 O(O 2 CR) 6 complex possesses a central O atom, which is surrounded by four Zn atoms in a perfect tetrahedral coordination.…”
Section: Resultsmentioning
confidence: 99%
“…At lower temperatures such as RT, the organozinc compound existed in a form of linear chain polymer as verified by the IR spectra analyzed above. When annealed at a higher temperature (≥120 °C), this kind of linear chain polymer can be converted to zinc oxocarboxylates (Scheme b) 40. Such zinc oxocarboxylates are more feasible to crystallize than the linear polymer of zinc carboxylates.…”
Section: Resultsmentioning
confidence: 99%